THE HYBRIDITY AND MIMICRY IN MY SON THE FANATIC SHORT STORY (A POST COLONIAL STUDY) - Ermawati, Atik; Rahmawati, Fauziah Indah Dini; Pahlevi, Reza Ayub (Universitas Negeri Manado, 2023)
Contemporary American literature reflects the cultural, social, and political changes that occurred in the United States during this period and encompasses a wide variety of genres, styles, and themes. In the realm of contemporary American literature, short stories offer an intriguing space for exploration, particularly in the context of the concepts of hybridity and mimicry. One notable work in Contemporary American Literature is the short story My Son the Fanatic (1997), which presents a rich narrative about hybridity and mimicry amidst the complexities of cultural identity. This research aims to describe how the characters in the short story create complex forms of identity by combining Pakistani culture and Western cultural influences, using Homi K. Bhabha's (1994) post colonial approach, namely, hybridity and mimicry. The research results reveal that Ali attempts to express himself as a hybrid product, bridging traditional Pakistani culture and modern Western culture, while Parvez represents a more modern culture and closely imitates Western culture in an effort to adhere to existing trends and norms. The conclusions of this research underscore the significance of understanding how processes of hybridity and mimicry influence the formation of individual and community identities.